Study of Feasibility Integrated Agroindustry Development Unit Black Grass Jelly Powder (Mesona palustris) in Province of East Java - Irvan Adhin Cholilie; Susinggih Wijana; Bambang Dwi Argo (Graduate Program, 2017)
Potential of black grass jelly plant in Indonesia is very prospective. These plants grow in areas such as Malang East Java, Pacitan, Magetan and Ponorogo. In 2010 the production of dried black grass jelly of 568 tons with a total productivity of 8.6 tons / year. Location selection of the plant with a score weighting method produces the highest value of 4,16 for the city of Surabaya, so the establishment of the plant will be held in Surabaya. Therefore, it is necessary the application of a suitable drying models for this factory that is tunnel dryer based on the results of research and with the highest value is 4,281. To ensure the availability of black grass jelly dried leaves as raw materials of black grass jelly powder it is necessary to establish a partnership between farmers and companies. The partnership pattern that works best for black grass jelly powder factory is a partnership “inti plasma”. It is based on research with the results of the assessment and weighting by using pairwise comparison and rating scale, the value of the highest weight in the “inti plasma” partnership with a value of 4,893. By implementing this partnership will allow the factory to obtain raw materials easily and is more economical and can always be available throughout the year for partnering with farmers. Keywords: black grass jelly powder, drying method, financial feasibility analysis, partnership patterns